2022
DOI: 10.1111/mms.12917
|View full text |Cite
|
Sign up to set email alerts
|

Vocalization of Bryde's whales (Balaenoptera edeni) in the Beibu Gulf, China

Abstract: The presence of Bryde's whales (Balaenoptera edeni) in the Beibu Gulf, China has been reported since 2016. In the current study, in situ Bryde's whale vocalizations were recorded. Bouts of frequency modulated repetitive and diversified calls were recorded. Repetitive calls were recorded when 1–3 whales were present within 2 km of the boat and were probably emitted by a single whale and functioned as contact calls. Repetitive calls were divided into biphonation downswept tonals and downswept tonals. Diversified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Conservation management typically focuses on protecting wildlife habitats associated with key behavioral processes, such as resting, socializing, breeding, birthing, and feeding, while also minimizing possible anthropogenic impacts ( Reynolds III et al, 2009 ; Wang et al, 2019 , 2022 , 2021c , 2014b ). Knowing the timing and location of these vital behavioral processes is essential for mitigating anthropogenic impacts on endangered animal populations ( Smith et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conservation management typically focuses on protecting wildlife habitats associated with key behavioral processes, such as resting, socializing, breeding, birthing, and feeding, while also minimizing possible anthropogenic impacts ( Reynolds III et al, 2009 ; Wang et al, 2019 , 2022 , 2021c , 2014b ). Knowing the timing and location of these vital behavioral processes is essential for mitigating anthropogenic impacts on endangered animal populations ( Smith et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…No studies of Bryde's whales call repertoires are available from southern Africa but we identified a call similar to published Bryde's whale calls (Wang et al . 2022) from other regions and thus use the conservative term Bryde's-like. The call was down-swept and significantly higher in frequency than the sei calls identified.…”
Section: Resultsmentioning
confidence: 99%
“…Thomisch et al ., 2019). Very few studies visually confirmed the species of whale recorded (McDonald et al ., 2005; Risch et al ., 2014; Wang et al 2022), reflecting the challenging nature of studying these wide-ranging animals that have calls which can be detected tens to hundreds of kilometres away. Species which likely occur in the study area but with poorly known vocalizations include pygmy right whales (with only a single paper published globally; Dawbin and Cato, 1992), Bryde's and dwarf minke whales.…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern North Pacific in the Southern California Bight, the Be4 call type has also been detected seasonally from August-December over multiple years (Kerosky et al, 2012). Different call types have been recorded in the western North Pacific off Japan and China (Oleson et al, 2003;Wang et al, 2022) and a potential Bryde's whale pulsed call has been detected in the Mariana Archipelago (Szesciorka et al, 2023). In the western South Pacific, calls similar to Be3 and the low burst tonal described by Oleson et al (2003) and Heimlich et al (2005), respectively, were recorded year-round near New Zealand and in the Lau Basin, near Fiji and Tonga (McDonald, 2006;Brodie and Dunn, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Finally, in the central North Pacific, call types similar to the Be3 were recorded and individual calling whales were tracked over the U.S. Navy's Pacific Missile Range Facility (PMRF) off the coast of Kaua'i, Hawai'i (Helble et al, 2016). The call types recorded in the Eastern Tropical Pacific, central North Pacific, and western South Pacific had average inter-call intervals (ICIs) of 0.3-6.3 min, with all but one call type ICI greater than 1 min (Oleson et al, 2003;Heimlich et al, 2005;Brodie and Dunn, 2015;Helble et al, 2016), while those in the western North Pacific had considerably shorter ICIs of 2-17 s (Oleson et al, 2003;Wang et al, 2022). It is unknown if these various call types correspond to different populations of Bryde's whales or if individual Bryde's whales produce a variety of call types throughout their range or at different times of the year.…”
Section: Introductionmentioning
confidence: 99%